Enhancement of antioxidant and skin moisturizing effects of olive oil by incorporation into microemulsions - Wantida Chaiyana (2018)
© 2016, © The Author(s) 2016. The aims of the present study were to develop olive oil microemulsions and characterize their antioxidant and skin moisturizing properties. The acid, iodine, and saponification values of olive oil were 0.38 ± 0.01 mg potassium hydroxide/g, 88.2 ± 5.9 mg iodine/g, and 192.2 ± 1.4 mg potassium hydroxide/g, respectively. Pseudoternary phase diagrams, constructed using the water titration method, produced suitable microemulsions: microemulsion 1 (10% olive oil, 64% Tween 85, 16% propylene glycol, and 10% water) and microemulsion 2 (10% olive oil, 64% Tween 85, 16% ethanol, and 10% water). Microemulsions 1 and 2 exhibited Newtonian flow behavior with internal droplet sizes of 443.60 ± 27.66 nm and 139.37 ± 12.15 nm, respectively. Their in vitro antioxidant and skin moisturizing properties were investigated in comparison with native olive oil. Microemulsion 2 possessed the highest significant antioxidant effect (p < 0.05) giving half maximal inhibitory concentration values in radical-scavenging activity against 1,1-diphenyl-2-picrylhydrazyl and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) of 4.78 ± 1.25 mg/mL and 14.85 ± 11.18 mg/mL, respectively. The lipid peroxidation inhibition of microemulsion 2 was comparable to native olive oil, whereas the skin moisturizing effect of microemulsion 1 was comparable to the well-known skin moisturizer, hyaluronic acid. In conclusion, microemulsions enhanced both antioxidant and skin moisturizing effects and were attractive formulations for using as a cosmetic or drug delivery system.